Development of sequence characterized amplified region markers for identification of Azospirillum brasilense Az39 - Coniglio, Nayla Anahí (2020)
Azospirillum brasilense Az39 has been used since more than 30 years by several companies in South America for biofertilizers production. This strain may promote plants growth and development, as well as the ability of inoculated plants to tolerate environmental stresses, which determines an increase in the productivity under field conditions. At present, there are no protocols in Argentina to confirm the identity of Az39 in commercial products; however, such biofertilizers are formulated almost exclusively with this strain. Therefore, the objective of this paper was to develop a molecular methodology that allows the accurate identification of A. brasilense Az39. Using the complete genome sequence and several bioinformatics tools, fragments of DNA present only in the Az39 genome were recognized. A set of PCR primers to amplify these sequences were designed, and the specific products were observed only in the strain of our interest. The sensitivity of the methodology was evaluated, where the strain could be detected up to a titer of 105 CFU/ml (4.5 ng/μl ADN) or 102 CFU/ml (0.88 ng/μl DNA) or in a minimal concentration of 0.098 ng/μl DNA, depending on the DNA extraction methodology used. Primers were tested against direct samples of commercial inoculants and cultures, in both cases there were specifics products, both in direct samples and in confirmatory tests from isolated colonies from those products. The procedure presented in this paper allows the accurate identification of A. brasilense Az39 in pure cultures, mixtures of microorganisms, and commercial biofertilizers.